A matter of security : the application of attachment theory to forensic psychiatry and psychotherapy - Pfäfflin, Friedemann; Adshead, Gwen (Forensic focus ;, 2004)
As a psychodynamic theory of both normal development and psychopathology, attachment theory has particular utility for forensic psychiatry. A Matter of Security provides an account of the development of arousal and affect regulation, which offers a new way of thinking about mental disorders in offenders. This book also discusses the development of personality in terms of interpersonal functioning and relationships with others, which is essential to understanding both interpersonal violence and abnormal personality development. Attachment theory also offers a model of therapeutic work with pati.